Hemochromatosis-causing mutations C282Y and H63D are not risk factors for atherothrombotic cerebral infarction - Hruskovicová, Helena; Milanez, Tomaz; Kobal, Jan; Potisk, Karmen Peterlin; Petrovic, Danijel; Peterlin, Borut (Medical science monitor, 2005)
It has been suggested that iron metabolism may be involved in the pathogenesis of atherothrombotic cerebral infarction (ACI). The C282Y and H63D mutations in the hemochromatosis (HFE) gene are associated with increased serum iron levels and net iron accumulation. The aim of this study was to test the hypothesis that the C282Y and H63D mutations in the HFE gene are risk factors for ACI in a Slovene population. The C282Y and H63D HFE gene mutations were tested in 96 Caucasian patients who had suffered an acute cerebral infarction, later confirmed as ACI, and 115 control subjects. Genotypes were determined by electrophoresis of the DNA digestion products from RsaI (C282Y) and MboI (H63D). We failed to demonstrate that the C282Y and H63D mutations were risk factors for ACI in Caucasians. The percentage of C282Y and H63D genotypes (dominant model) in ACI-cases (C282Y: 7.3%, n=7; H63D: 28.1%, n=27) did not differ significantly (P=0.9 and P=0.7 respectively) from that of the controls (C282Y: 7.0%, n=8; H63D: 26.1%, n=30). Logistic regression analysis revealed that arterial hypertension, diabetes, and cigarette smoking are independent risk factors for ACI, whereas the C282Y and H63D HFE gene mutations are not. We provided evidence that the C282Y and H63D HFE gene mutations were not risk factors for ACI in this Slovene population.